1987
DOI: 10.1007/bf00187264
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nicotine on locomotor behavior in non-tolerant rats: a multivariate assessment

Abstract: Previous studies assessing the effects of nicotine on the locomotion of non-tolerant rats have yielded mixed results. High doses of nicotine have been reported to decrease both rearing and locomotor behavior. Low doses of nicotine have either decreased or had no effect on rearing, and have been reported to increase, decrease or have no effect on ambulation. The present study utilized ten indices of locomotor behavior collected simultaneously, which allowed for a more fine-grained analysis of locomotor behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Previous studies assessing the acute effects of i.p. nicotine administration upon locomotion have yielded mixed results (either an increase or a decrease have been reported, see Jerome and Sanberg 1987;Clarke and Kumar 1983). Present data suggest an age-related dissociation in nicotine effects, which can possibly be ascribed to age-related discontinuities in the functional maturation of drug-targeted brain systems (Naeff et al 1992;Teicher et al 1995;Trauth et al 1999).…”
Section: Behavioral/pharmacological Effects Of Oral Nicotinementioning
confidence: 72%
“…Previous studies assessing the acute effects of i.p. nicotine administration upon locomotion have yielded mixed results (either an increase or a decrease have been reported, see Jerome and Sanberg 1987;Clarke and Kumar 1983). Present data suggest an age-related dissociation in nicotine effects, which can possibly be ascribed to age-related discontinuities in the functional maturation of drug-targeted brain systems (Naeff et al 1992;Teicher et al 1995;Trauth et al 1999).…”
Section: Behavioral/pharmacological Effects Of Oral Nicotinementioning
confidence: 72%
“…Interestingly, when sensitization curves were analyzed, both sexes demonstrated a decrease in vertical rearing when given nicotine, but there were no effects of ontogenetic drug treatment. Both Jerome and Sanberg (1987) and Ksir (1994) have shown that nicotine produced a significant decrease of vertical rearing, although only males were analyzed in both studies. Thus, it appears that in terms of the analysis of sensitization curves, the present results are consistent with these findings but extend these results to include an analysis of both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine can either increase or decrease locomotion. There is debate in the literature as to what determines the direction of nicotine’s locomotor effects (Jerome and Sanberg 1987), so it is not surprising that the role of age is also debated. Two studies observed increased locomotion in adolescents but decreased locomotion in adults (Vastola et al 2002; Cao et al 2007a).…”
Section: Early Drug Exposurementioning
confidence: 99%